Analysis of lubricating oil in internal combustion engines of electrical power generation plant - Pozo-Morejón, Juan A.; Martínez-Jiménez, Boris L.; Rodríguez-Rico, Iván L.; Martínez-Martínez, Reinaldo; Herrera-Artiles, Arnaldo M.; Cabral Leite, Jandecy (Rev. Téc. Fac. Ing. Univ. Zulia, 2016)
In the present work, an integrated quality analysis process of the lubricating oil used in stationary diesel engines of electric power plants is implemented. This process includes a continuous monitoring of relevant variables through the well-known methodology SACODE with the following modifications: changes in variable limits and evaluation of kinematic viscosity and TBN by using Fuzzy logic. The method of analysis was automated by the implementation of the software SOFTLUB on the MATLAB platform. The uses of SOFTLUB allowed graphing historical results of oil quality parameters, calculating and updating its limits, quality assessment and also predicting future behavior of oil viscosity and TBN, in order to support maintenance decision making in power plants.